2014
DOI: 10.1007/s11698-014-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Good for girls or bad for boys? Schooling, social inequality and intrahousehold allocation in early twentieth century Finland

Abstract: Apart from the commonly emphasized historical or cultural explanations, was there an economics behind the early, extensive schooling of girls in Europe's Nordic periphery? This article analyses factors behind the emerging female majority in secondary schooling in early twentieth century Finland through resource allocation within households. We argue that a significant part of the female educational advantage can be explained with a classic unitary Beckerian schooling investment model. We apply an Engel specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Firstly, if money for treatment followed morbidity also in the age group where female excess mortality was discernible, it would be hard to reconcile this with the notion that the health risk itself was caused by neglect within the same households that were allocating their scarce resources to medical care. Secondly, recent analysis has shown that girls from worker families in this age group were, on average, given more resources for education than boys (Saaritsa & Kaihovaara 2016), contradicting notions of parental exploitation or disinvestment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Firstly, if money for treatment followed morbidity also in the age group where female excess mortality was discernible, it would be hard to reconcile this with the notion that the health risk itself was caused by neglect within the same households that were allocating their scarce resources to medical care. Secondly, recent analysis has shown that girls from worker families in this age group were, on average, given more resources for education than boys (Saaritsa & Kaihovaara 2016), contradicting notions of parental exploitation or disinvestment.…”
Section: Discussionmentioning
confidence: 93%
“…Less wealthy socioeconomic groups were more likely to send girls than boys to secondary education when they could, because the immediate opportunity cost in lost earnings was lower and relative expected returns higher. However, enrolment was still generally low (Saaritsa & Kaihovaara 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Following in their footsteps, other scholars have used historical household budgets to study a range of themes. These include diet and nutrition (Vecchi and Coppola, 2006;Logan, 2006Logan, , 2009Gazeley and Horrell, 2013;Gazeley and Newell, 2015;Lundh, 2013), inequality and poverty (Rossi et al 2001, Amendola andVecchi, 2016), intra-household dynamics (Horrell and Oxley, 2013;Saaritsa and Kaihovaara, 2016;Scott, Walker and Miskell, 2015;Guyer, 1980), labor force participation (Baines and Johnson, 1999), child labor (Moehling, 2001(Moehling, , 2005, consumption behavior (Scott and Walker, 2012;Lilja and Bäcklund, 2013), agriculture and home-production (Federico, 1986(Federico, , 1991, economies of scale and child well-being (Hatton and Martin, 2010;Logan, 2011), and informal transfers of cash and goods between households (Saaritsa, 2008(Saaritsa, , 2011.…”
Section: Household Budgets In Historymentioning
confidence: 99%
“…Most respondents considered 12 to be a proper age to start working and thought that children who were not taught a craft at a young age would suffer the consequences during their adult lives. 245 Factory work was in this way considered to be an investment in human capital. However, one producer said: "[i]n general, it is not the producer's desire to hire such young labourers, but it is a request from the 238 Dyhouse, 'Working-class'; Mokyr, 'Why "more work for mother"?'.…”
Section: Childrenmentioning
confidence: 99%